2020
DOI: 10.3390/cancers12082085
|View full text |Cite
|
Sign up to set email alerts
|

Plasmacytoid Dendritic Cell Impairment in Metastatic Melanoma by Lactic Acidosis

Abstract: The introduction of targeted therapies and immunotherapies has significantly improved the outcome of metastatic melanoma (MM) patients. These approaches rely on immune functions for their anti-melanoma response. Plasmacytoid dendritic cells (pDCs) exhibit anti-tumor function by production of effector molecules, type I interferons (I-IFNs), and cytokines. Tissue and blood pDCs result compromised in MM, although these findings are still partially conflicting. This study reports that blood pDCs were dramatically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 87 publications
(130 reference statements)
0
36
0
Order By: Relevance
“…Exposure of lactic acidosis to dendritic cells impaired both the viability and functions of dendritic cells. [ 61 ] Based on these findings, we speculate LDH may exert similar functions to the activation of PD-1/PD-L1 pathway and therefore, the presence of a high LDH level in melanomas may antagonize the therapeutic effects of PD-1/PD-L1 inhibitors and lead to a poor prognosis.…”
Section: Discussionmentioning
confidence: 86%
“…Exposure of lactic acidosis to dendritic cells impaired both the viability and functions of dendritic cells. [ 61 ] Based on these findings, we speculate LDH may exert similar functions to the activation of PD-1/PD-L1 pathway and therefore, the presence of a high LDH level in melanomas may antagonize the therapeutic effects of PD-1/PD-L1 inhibitors and lead to a poor prognosis.…”
Section: Discussionmentioning
confidence: 86%
“…Increased lactic acidosis can compromise both the numbers and functions of dendritic cells. [ 81 ] Qiao et al [ 82 ] evaluated the efficacy of using LDH inhibitor oxamate and pembrolizumab alone or in combination in an NSCLC humanized mouse model. They found that both oxamate and pembrolizumab monotherapy significantly delayed tumor growth.…”
Section: Discussionmentioning
confidence: 99%
“…DCs and macrophages exposed to TLR-ligands produce markedly higher levels of proinflammatory cytokines and type-I interferons (IFN). In contrast, lactate-conditioned DCs and macrophages do not release immunostimulatory cytokines; instead, they express higher levels of IL-10 in response to TLR ligands ( 53 55 , 57 , 58 ). The TME contains higher levels of immune regulatory factors such as IL-10, retinoic acid (RA), and TGF-β that actively suppress differentiation and expansion of tumor-specific effector T cells ( 114 , 115 ).…”
Section: Regulation Of Immune Regulatory and Inflammatory Factors By Lactatementioning
confidence: 94%